Modeling, Simulation, and Stabilization of a Two-Wheeled Inverted Pendulum Robot Using Hybrid Fuzzy Control - Made Rahmawaty (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2021)
Two wheels inverted pendulum robot has the same characteristics as an inverted pendulum, which are unstable and nonlinear. Nonlinear systems can often be linearized by approximating them by a linear system obtained by expanding the nonlinear solution in a series, and then linear techniques can be used. Fuzzy logic control is the famous nonlinear controller that researchers have used to analyze the performance of a system due to the easiness of understanding the nature of the controller. This research discusses two wheels inverted pendulum robot design using hybrid fuzzy control. There are two types of fuzzy control: Fuzzy Balanced Standing Control (FBSC) to maintain stability and Fuzzy Traveling and Position Control (FTPC). Based on Takagi-Sugeno (T-S) fuzzy model on two wheels inverted pendulum robot, FBSC control used Parallel Distributed Compensation (PDC) with pole placement technic. Based on two wheels inverted pendulum robot movement characteristics, FTPC was designed using Mamdani Fuzzy architecture. FTPC control is used to help FBSC maintain robot stability and adjust to the desired position. The simulation result shows that the controller for two wheels inverted pendulum robot can stabilize pendulum angle in 0 radian and close to the desired position.